Profile of Multidrug Resistance and Methicillin-Resistant Staphylococcus aureus (MRSA) isolated from cats in Surabaya, Indonesia - DANIAH ASHRI AFNANI; NURULLAH FATIH; MUSTOFA HELMI EFFENDI; WIWIEK TYASNINGSIH; ASWIN RAFIF KHAIRULLAH; SHENDY CANADYA KURNIAWAN; OTTO SAHAT MARTUA SILAEN; SANCAKA CHASYER RAMANDINIANTO; AGUS WIDODO; KATTY HENDRIANA PRISCILIA RIWU (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Afnani DA, Fatih N, Effendi MH, Tyasningsih W, Kairullah AR, Kurniawan SC, Silaen OSM, Ramandianto SC, Widodo A, Hendriana K, Riwu KHP. 2022. Profile of Multidrug Resistance and Methicillin-Resistant Staphylococcus aureus (MRSA) isolated from cats in Surabaya, Indonesia. Biodiversitas 23: 5703-5709. Methicillin-Resistant Staphylococcus aureus (MRSA) is the name given to Staphylococcus aureus that has multidrug-resistance (MDR) characteristics and is resistant to ?-lactam drugs. Compared to other livestock, companion animals have been mentioned as potential MRSA reservoirs more frequently. This study aimed to identify MDR and detects MRSA strains from cats in Surabaya. A total of 150 nasal swab of cats were taken from several clinics and veterinary hospital. Samples were swabbed using Amies Medium Transport then identified using microbiological standard method. Kirby-Bauer diffusion method was performed for S. aureus antibiotic resistance profile on five different antibiotic discs. As a confirmatory test for MRSA, S. aureus isolates that were resistant to cefoxitin continued to grow on Oxacillin Resistance Screening Agar Base (ORSAB). The findings of the isolation and identification and process revealed 18 (12%) S. aureus isolates. The antibiotic resistance test revealed 3 (2%) MDR S. aureus isolates and 4 (2.6%) MDR S. aureus isolates that were ORSAB positive. It has been discovered that there are MDR and MRSA S. aureus isolates. It could be used as an indicator of irrational usage of antibiotics and it explained that cats could be source of infection to public health.